2021
DOI: 10.1051/aacus/2021001
|View full text |Cite
|
Sign up to set email alerts
|

On the influence of non-individual binaural cues and the impact of level normalization on auditory distance estimation of nearby sound sources

Abstract: Nearby sound sources provide distinct binaural cues, mainly in the form of interaural level differences, which vary with respect to distance and azimuth. However, there is a long-standing controversy regarding whether humans can actually utilize binaural cues for distance estimation of nearby sources. Therefore, we conducted three experiments using non-individual binaural synthesis. In Experiment 1, subjects had to estimate the relative distance of loudness-normalized and non-normalized nearby sources in stati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 40 publications
(112 reference statements)
2
3
0
Order By: Relevance
“…Our experiments, as well as the study by Rummukainen et al [14], might indicate that correct reproduction of intensity as the primary and strongest distance cue is, in most cases, sufficient for a plausible representation of nearby sound sources in dynamic multimodal virtual environments. In line with this, experiments on distance perception revealed that, if available, the intensity cue dominates auditory distance estimation and masks the much more subtle near-field cues [11,13]. Furthermore, a multimodal AR experience, as in the present study, provides proprioceptive and visual cues in addition to auditory cues, enhancing auditory localization and providing listeners with more information to judge the plausibility of a virtual sound source reliably.…”
Section: Resultssupporting
confidence: 81%
See 4 more Smart Citations
“…Our experiments, as well as the study by Rummukainen et al [14], might indicate that correct reproduction of intensity as the primary and strongest distance cue is, in most cases, sufficient for a plausible representation of nearby sound sources in dynamic multimodal virtual environments. In line with this, experiments on distance perception revealed that, if available, the intensity cue dominates auditory distance estimation and masks the much more subtle near-field cues [11,13]. Furthermore, a multimodal AR experience, as in the present study, provides proprioceptive and visual cues in addition to auditory cues, enhancing auditory localization and providing listeners with more information to judge the plausibility of a virtual sound source reliably.…”
Section: Resultssupporting
confidence: 81%
“…Consistently, the synthesized near-field HRTFs show strong low-frequency ILDs for lateral directions at close distances and a significant increase in ILD with increasing frequency. Overall, the described characteristics of the synthesized HRTFs are very similar to those of measured near-field HRTFs [5,11,41], confirming that the synthesis yields correct results. In particular, the low-frequency horizontal plane ILDs and ITDs of the synthesized near-field HRTFs are nearly identical to those of measured Neumann KU100 near-field HRTFs from [5] (see Fig.…”
Section: Methodssupporting
confidence: 63%
See 3 more Smart Citations